Analisis Kinerja Keuangan Perusahaan Sebelum dan Setelah Penyebaran Covid-19 (Studi Kasus pada Perusahaan yang Tercatat di Bursa Efek Indonesia) - Listya Devi Junaidi; Umar Hamdan Nasution (Universitas Batanghari Jambi, 2022)
The expansion of the Covid-19 pandemic is not only bad for people's health, but it's also bad for the country's economy, both at home and abroad. This situation has harmed Indonesian businesses, as customers' spending power has declined as a result of constrained activity and numerous layoffs. This has a significant impact on the company's financial performance. This study attempts to investigate the changes in financial performance of enterprises listed on the Indonesia Stock Exchange (IDX) before and after the covid-19 pandemic, as measured by financial ratios such as Current Ratio (CR), Return On Assets (ROA), and Total Debt to Asset Ratio (DAR). The year 2019-2020 was chosen as the research period. The research population covers all 713 businesses that will be listed on the Indonesia Stock Exchange in 2020. Purposive sampling was utilized in the sample selection approach, which yielded 441 firms. The paired sample t-test and the Wilcoxon signed rank test were employed to analyze the data, which had already been checked for normality. According to the findings of the data analysis, there is no difference in the value of the current ratio and the value of the debt to assets ratio in companies listed on the IDX before and after the covid-19 spread. There is, however, a variation in the value of the return on assets ratio of companies listed on the IDX before and after the COVID-19 spread.